Crowned Dens Syndrome: A Case Report and Literature Review - Huang, Pan; Xu, Min; He, Xiao-Ying (Frontiers in Medicine, 2022)
Crowned Dens Syndrome (CDS) is the leading cause of acute neck pain and a major cause of reduced neck mobility. DiagnosisThe diagnosis of CDS is challenging due to theas clinicians currently have limited awareness of clinicians of the symptoms of the disease. ThisIn this article reports, we report a case of odontoid syndrome as a reference for the diagnosis and treatment of CDS.